The Clinical Characteristics, Patterns of Recurrence, and Long-Term Survival Outcomes of Dual-Phenotype Hepatocellular Carcinoma After Curative Liver Resection - Yu ZC; Fang ZK; Yu Y; Liu SY; Wang KD; Shi ZJ; Jin LM; Huang XK; Lu Y; Shen GL; Liu JW; Huang DS; et al. (Journal of Hepatocellular Carcinoma)
Zi-Chen Yu,1,2 Zheng-Kang Fang,1,2 Yang Yu,3 Si-Yu Liu,4 Kai-Di Wang,1,5 Zhe-Jin Shi,1,5 Li-Ming Jin,1 Xiao-Kun Huang,1,2 Yi Lu,1 Guo-Liang Shen,1 Jun-Wei Liu,1 Dong-Sheng Huang,1 Cheng-Wu Zhang,1 Lei Liang1 1Department of Hepatobiliary & Pancreatic Surgery and Minimally Invasive Surgery, General Surgery, Cancer Center, Zhejiang Provincial People’s Hospital, Affiliated People’s Hospital, Hangzhou Medical College, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Postgraduate Training Base Alliance of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 3Department of Urology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 4Department of Laboratory Medicine, The Key Laboratory of Imaging Diagnosis and Minimally Invasive Interventional Research of Zhejiang Province, Zhejiang University Lishui Hospital, Lishui, Zhejiang, People’s Republic of China; 5Department of the second School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Lei Liang, General Surgery, Cancer Center, Department of Hepatobiliary and Pancreatic Surgery and Minimal Invasive Surgery, Zhejiang Provincial People’s Hospital, Affiliated People’s Hospital, Hangzhou Medical College, Hangzhou, Zhejiang, 310014, People’s Republic of China, Email liangl1992@hotmail.comBackground & Aims: Dual-phenotype hepatocellular carcinoma (DPHCC) is discernible from classical HCC (CHCC) in its morphology and is characterized by the co-expression of both CHCC and cholangiocyte markers. This study aimed to clarify the difference between DPHCC and CHCC after surgery.Methods: Patients with HCC after surgery were collected. The clinical characteristics, patterns of recurrence, and survival outcomes of patients with DPHCC and CHCC were compared. Multivariate analyses were used to determine the independent risk factors that influence the prognosis of patients.Results: Patients with DPHCC (n = 141) account for 26% of the total patients (n = 541). Compared to patients with CHCC, patients with DPHCC are significantly associated with incomplete capsules, microvascular invasion, and poor differentiation (all P < 0.05). Compared to patients with CHCC, the 5-year overall survival (OS) (56% vs 43%) and recurrence-free survival (RFS) (35% vs 28%) are lower in patients with DPHCC. Meanwhile, among patients with tumor recurrence after surgery, patients with DPHCC have a higher proportion of advanced-stage tumors, and extrahepatic metastasis (all P < 0.05). Moreover, multivariate analysis showed that DPHCC is an independent risk factor for both OS (HR 1.399, 95% CI 1.061– 1.845, P = 0.017) and RFS (HR 1.313, 95% CI 1.033– 1.669, P = 0.026).Conclusion: DPHCC, an aggressive HCC subtype with poor differentiation and high invasiveness, shows inferior RFS and OS post-liver resection compared to CHCC. Clinicians’ recognition and addressing of its unique challenges can improve DPHCC patients’ prognosis and QoL.Keywords: hepatocellular carcinoma, dual-phenotype, recurrence, overall survival, prognosis